Developing Student Abilities Through Classroom Management: Principles, Components and Role of the Teacher - Sekar Kurnia Rahmadani; Neviyarni S; Herman Nirwana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The purpose of this research is to find out what classroom management is, to know the objectives of class management, to know the principles of class management, to know the components of class management and the scope of class management. The research method uses the Systematic Literature Review (SLR) method or systematic literature review, namely a literature review method that identifies, examines, evaluates and interprets all available research. Researchers conducted a review and identified journals in a structured manner that in each process followed predetermined steps. The conclusion of the research results on classroom management is that there are still many problems related to ongoing teaching and learning activities. Often there are various complaints or criticisms from students, parents or teachers regarding the implementation of these teaching activities. These complaints actually do not need to occur or at least can be minimized, if all parties can play a role, especially teachers as class managers in their proper functions. Meanwhile, the understanding of classroom management still seems to be wrong. Often class management is understood as the arrangement of classrooms relating to facilities such as seating, bookcases and teaching aids.